Impact of Covid-19 on aquaculture and fisheries in ASEAN countries: some aspects of challenges, mitigations for future strategies in Malaysia - Chowdhury, Ahmed Jalal Khan; John, Akbar B; Abdullah, Rose; Musa, Najiah; Ashraf, Muhammad Aqeel (Desalination Publications, 2021)
This review paper discusses some of the challenges on the effects of COVID-19 on aquaculture and fisheries and their mitigations and strategies in ASEAN perspectives with special emphasis on Malaysia due to significant impacts of COVID-19 occurred in this country’s enormous aquaculture and fishing industries. Substantial factors within fishery systems, as well as ecological and social impacts outside their control, such as climate change, chronic pollution, resource degradation, fluctuating commodity prices and changes in management strategies that can asymmetrically affect different communities, stress fish culturists and fisher-folk communities. COVID-19’s broken food supply chain and shrinking market have certainly impacted everyone in the fishing and aquaculture business, with small-scale fishermen being the most susceptible. During COVID19 pandemic in ASEAN countries, it was discovered that the potential effects on agricultural sectors in Malaysia needed to be protected in order to defend the well-being of farmers, breeders, fishers, and workers, the majority of whom are low-income earners. The relevant authorities have created different supply chains and expand supply sources to maintain revenue in the event of a national economic downturn through traditional marketing channels. The Post COVID-19 monitoring should be undertaken as a model role based on the Malaysian scenario to gain a quick grasp of the food security and livelihood situation of all fishing communities. As a result, a national platform is urgently needed to boost production, supply, and marketing integration so that the fisheries and aquaculture products may be traded efficiently. Nevertheless, transparency in policy responses, as well as regional and international cooperation, will support to build trust in the future of fish value chains and markets. Furthermore, these real-world lessons will make it easier to learn from the pandemic crisis to improve the sustainability and viability of fisheries and aquaculture industries in ASEAN countries and global as well.